Planar thermoelectric conversion element and manufacturing method thereof

The flat-type thermoelectric conversion element with magnesium-based semiconductor films and silicon nitride layers addresses the need for improved microscopic applications, offering high-yield and durable performance for IoT devices by enhancing thermoelectric characteristics through precise manufacturing methods.

JP7627034B2Active Publication Date: 2025-02-05NAT INST FOR MATERIALS SCI
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021103708
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-06-23
Publication Date
2025-02-05
Estimated Expiration
2041-06-23

AI Technical Summary

Technical Problem

Existing thermoelectric conversion elements are not suitable for microscopic applications and require improvements in manufacturing methods to enhance thermoelectric characteristics and durability for IoT devices.

Method used

A flat-type thermoelectric conversion element is developed with a laminated structure comprising an insulating substrate, a pair of thermoelectric films, and electrodes, utilizing magnesium-based thermoelectric semiconductor films and silicon nitride films to improve adhesion and thermoelectric performance, and a manufacturing method using lithography technology to ensure precise patterning without peeling.

Benefits of technology

The solution provides a high-yield, durable, and efficient thermoelectric conversion element with excellent thermoelectric characteristics, suitable for IoT devices as both an independent power supply and sensor element, maintaining performance under varying temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007627034000001
    Figure 0007627034000001
  • Figure 0007627034000002
    Figure 0007627034000002
  • Figure 0007627034000003
    Figure 0007627034000003
Patent Text Reader

Abstract

To provide a planar thermoelectric conversion element advantageous to the microfabrication process, and a method for manufacturing the same.SOLUTION: A planar thermoelectric conversion element has an insulating substrate, at least a pair of first and second thermoelectric thin films located on the insulating substrate, and electrodes connecting the first and second thermoelectric thin films, the first thermoelectric thin film has a magnesium-based thermoelectric semiconductor film and a silicon nitride film located thereon, and the electrode electrically connects the magnesium-based thermoelectric semiconductor film of the first thermoelectric thin film and the second thermoelectric thin film.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a planar thermoelectric conversion element and a manufacturing method thereof. [Background technology]

[0002] In an IoT (Internet of Things) society where advanced internet is widespread, there is a demand for IoT devices with built-in independent power sources that can operate independently from outside. Thermoelectric conversion elements, which have no mechanical moving parts and are maintenance-free, are one promising candidate for an independent power source for IoT devices. Thermoelectric conversion is also attracting attention as an application as a sensor element, and various applications of the element have been proposed. In order to effectively utilize thermoelectric conversion as an independent power source or sensor element for IoT devices, miniaturization and miniaturization are essential.

[0003] In recent years, Mg thin films have been used for thin-film thermoelectric elements to power IoT devices. 2 Epitaxial thin films represented by Sn have been reported (see, for example, Non-Patent Documents 1 and 2). It is expected that such epitaxial thin films can be used to develop planar thermoelectric conversion elements that enable microfabrication processes.

[0004] On the other hand, in the field of semiconductors, it is known to use a silicon nitride film as a protective film (see, for example, Patent Document 1). Patent Document 1 discloses forming a silicon nitride film with a thickness of 10 nm or less as a protective film for preventing oxidation and moisture absorption of a polycrystalline metal silicide layer. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2014 / 171146 [Non-patent literature]

[0006] [Non-Patent Document 1] Takashi Aizawa et al., J.Vac.Sci.Technol.A 37,061513,2019 [Non-Patent Document 2] Mariana SLLima et al., Japanese Journal of Applied Physics 60,SBBF06,2021 Summary of the Invention [Problem to be solved by the invention]

[0007] In view of the above, an object of the present invention is to provide a planar thermoelectric conversion element that is advantageous for microfabrication processes, and a manufacturing method thereof. [Means for solving the problem]

[0008] The flat thermoelectric conversion element of the present invention comprises an insulating substrate, at least a pair of a first thermoelectric thin film and a second thermoelectric thin film located on the insulating substrate, and electrodes connecting the first thermoelectric thin film and the second thermoelectric thin film, the first thermoelectric thin film comprising a magnesium-based thermoelectric semiconductor film and a silicon nitride film located on the magnesium-based thermoelectric semiconductor film, and the electrodes electrically connect the magnesium-based thermoelectric semiconductor film of the first thermoelectric thin film to the second thermoelectric thin film, thereby solving the above-mentioned problems. The magnesium-based thermoelectric semiconductor film is a doped or undoped Mg 2 X1 (X1 is at least one element selected from the group consisting of Si, Ge, Sn and Pb), Mg 3 X2 2 (X2 is Sb and / or Bi), and X3Mg 2 X4 2 (X3 is Ca and / or Yb, and X4 is Sb and / or Bi). The silicon nitride film may have a thickness in the range of 5 nm to 250 nm. An oxide layer may be present between the magnesium-based thermoelectric semiconductor film and the silicon nitride film. The oxide layer may be amorphous and contain oxygen and the elements that constitute the magnesium-based thermoelectric semiconductor thin film. The oxide layer may have a thickness in the range of greater than 0 nm to less than or equal to 50 nm. The magnesium-based thermoelectric semiconductor thin film may be oriented. The magnesium-based thermoelectric semiconductor thin film may have a thickness in the range of 50 nm to 10 μm. The electrode may have a laminated structure in which a chromium layer and a nickel layer are stacked in this order. The second thermoelectric thin film may be made of a metallic material or a semiconductor material. The second thermoelectric thin film may be an n-type material selected from the group consisting of bismuth (Bi), nickel (Ni), cobalt (Co) and constantan (Cu-Ni), or a p-type material which is antimony (Sb) and / or nichrome (Ni-Cr). The insulating substrate may be a glass substrate, a ceramic substrate, a silicon substrate, or a SiO 2 The substrate may be selected from the group consisting of a silicon substrate, a sapphire substrate, and a resin substrate. The planar thermoelectric conversion element may be further covered with a silicon nitride film, except for the electrodes connected to an external circuit. A method for manufacturing the above-mentioned flat thermoelectric conversion element of the present invention using lithography technology includes forming and patterning a first thermoelectric thin film in which a magnesium-based thermoelectric semiconductor film and then a silicon nitride film are laminated on an insulating substrate, forming and patterning a second thermoelectric thin film on the insulating substrate, and forming electrodes that electrically connect the magnesium-based thermoelectric semiconductor film and the second thermoelectric thin film, thereby solving the above-mentioned problem. The forming and patterning of the first thermoelectric thin film may further include exposing the magnesium-based thermoelectric semiconductor thin film to the atmosphere prior to forming the silicon nitride film. Forming and patterning the second thermoelectric thin film may form the second thermoelectric thin film at room temperature. Forming the electrode may further include forming a chromium layer and then a nickel layer. Following the formation of the electrodes, the electrodes may be covered with a further silicon nitride film, except for the electrodes that are to be connected to an external circuit. Effect of the Invention

[0009] The planar thermoelectric conversion element of the present invention comprises an insulating substrate, at least a pair of a first thermoelectric thin film and a second thermoelectric thin film located thereon, and electrodes connecting them, and the first thermoelectric thin film has a laminated structure of a magnesium-based thermoelectric semiconductor film and a silicon nitride film. Since the magnesium-based thermoelectric semiconductor film is used, the planar thermoelectric conversion element of the present invention has excellent thermoelectric properties, and since the silicon nitride film forms a good interface with the magnesium-based thermoelectric semiconductor film, deterioration of the element properties can be suppressed. Such a planar thermoelectric conversion element is applied to an independent power source or a sensor element for IoT devices.

[0010] The method for producing a flat thermoelectric conversion element of the present invention includes forming a first thermoelectric thin film, which is a laminate of a magnesium-based thermoelectric semiconductor film and then a silicon nitride film on an insulating substrate, and patterning the first thermoelectric thin film, forming a second thermoelectric thin film on the insulating substrate and patterning the second thermoelectric thin film, and forming electrodes that electrically connect the magnesium-based thermoelectric semiconductor film and the second thermoelectric thin film. By forming the silicon nitride film, adhesion to the resist is improved when using lithography technology, so that the resist does not peel off even during subsequent microfabrication processes such as exposure of the magnesium-based thermoelectric semiconductor thin film and electrode formation, resulting in excellent yield. [Brief description of the drawings]

[0011] [Figure 1] Schematic diagram showing a flat thermoelectric conversion element of the present invention. [Diagram 2] A flowchart showing the steps of manufacturing the flat thermoelectric conversion element of the present invention. [Diagram 3] A procedure showing the formation and patterning of a first thermoelectric thin film in step S210. [Figure 4]A procedure showing the formation and patterning of a second thermoelectric thin film in step S220. [Diagram 5] Procedure showing formation of electrodes in step S230 [Figure 6] 1 shows an Auger electron spectroscopy spectrum and a reflection electron diffraction image of a thin film sample of Reference Example 1. [Figure 7] FIG. 1 shows the element structure of a flat thermoelectric conversion element of Example 1. [Figure 8] A diagram showing details of the planar thermoelectric conversion element of Example 1. [Figure 9] Procedure for manufacturing the planar thermoelectric conversion element of Example 1 [Figure 10] FIG. 1 shows the results of microscopic observation of the flat thermoelectric conversion element of Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. Note that like elements are given like reference numerals and their description will be omitted.

[0013] FIG. 1 is a schematic diagram showing a flat thermoelectric conversion element of the present invention.

[0014] FIG. 1 shows a top view (A), an AA cross-sectional view (B), and a BB cross-sectional view (C) of the flat thermoelectric conversion element of the present invention. The flat thermoelectric conversion element (hereinafter, for simplicity, referred to as a thermoelectric conversion element) 100 of the present invention includes an insulating substrate 110, at least a pair of a first thermoelectric thin film 120 and a second thermoelectric thin film 140 located on the insulating substrate 110, and an electrode 150 connecting the first thermoelectric thin film 120 and the second thermoelectric thin film 140. Although FIG. 1 shows three pairs of the first thermoelectric thin film 120 and the second thermoelectric thin film 140, the number of pairs is not limited to this. The thermoelectric conversion element 100 of the present invention uses a thermoelectric thin film, and therefore can provide a small, thin, and therefore high-density and lightweight device.

[0015] Furthermore, in the thermoelectric conversion element 100 of the present invention, as shown in FIG. 1(B), the first thermoelectric thin film 120 includes a magnesium-based thermoelectric semiconductor film 121 and a silicon nitride film 130 located thereon. The thermoelectric conversion element 100 of the present invention has excellent thermoelectric characteristics that are advantageous in terms of controllability of carrier type and concentration by using the magnesium-based thermoelectric semiconductor film 121. Furthermore, since the silicon nitride film 130 adheres closely to the magnesium-based thermoelectric semiconductor film 121, a good interface is formed, and deterioration of the element characteristics can be suppressed. Furthermore, since the silicon nitride film 130 prevents the resist from peeling off, manufacturing using a photolithography technique described later is possible.

[0016] 1(C), in the thermoelectric conversion element 100 of the present invention, the electrode 150 electrically connects the magnesium-based thermoelectric semiconductor film 121 of the first thermoelectric thin film 120 to the second thermoelectric thin film 140. Since the magnesium-based thermoelectric semiconductor film 121 and the second thermoelectric thin film 140 are electrically connected, good electrical conductivity is obtained, resulting in excellent element characteristics.

[0017] Hereinafter, each component of the thermoelectric conversion element 100 of the present invention will be described. The insulating substrate 110 is not particularly limited as long as it has insulating properties and can form the first thermoelectric thin film 120 and the second thermoelectric thin film 140. Examples of the insulating substrate 110 include a glass substrate, a ceramic substrate, a silicon substrate, and a SiO 2 The substrate is selected from the group consisting of a silicon substrate, a sapphire substrate, and a resin substrate.

[0018] The glass substrate may be, for example, non-alkali glass, quartz glass, crystallized glass, borosilicate glass, high silicate glass, porous glass, or soda-lime glass.

[0019] The ceramic substrate may be, for example, aluminum nitride, silicon nitride, or alumina. These have excellent thermal conductivity, and therefore the thermoelectric conversion element 100 has excellent element characteristics.

[0020] The plane orientation of the sapphire substrate is not particularly limited, but is preferably C plane (0001). This allows the magnesium-based thermoelectric semiconductor 121 to be oriented, thereby obtaining high thermoelectric properties. For example, when the magnesium-based thermoelectric semiconductor 121 is Mg 2 If Sn, Mg 2 The Sn film has a (111) orientation.

[0021] The resin substrate may be, for example, a polyester substrate such as polyethylene terephthalate, polyethylene isophthalate, polyethylene naphthalate, polybutylene terephthalate, poly(1,4-cyclohexylene dimethylene terephthalate), or polyethylene-2,6-phthalenedicarboxylate, a polycycloolefin substrate, a polyimide substrate, a polycarbonate substrate, a polyether ether ketone substrate, a polyphenyl sulfide substrate, a polyacetal substrate, a polyamide substrate, a polyphenylene ether substrate, a polyolefin substrate, a polystyrene substrate, a polyarylate substrate, a polysulfone substrate, a polyether sulfone substrate, a fluororesin substrate, or a liquid crystal polymer substrate. By using such a resin substrate, a thermoelectric conversion element having flexibility can be provided.

[0022] The thickness of the insulating substrate 110 is not particularly limited, but is preferably in the range of 1 μm to 1 mm, and more preferably in the range of 5 μm to 0.5 mm. With such a thickness, it is easy to handle and a thin thermoelectric conversion element can be provided.

[0023] The magnesium-based thermoelectric semiconductor 121 is intended to mean a compound semiconductor containing magnesium, either doped or undoped, and having thermoelectric properties. Such a thermoelectric semiconductor 121 is preferably Mg 2 X1 (X1 is at least one element selected from the group consisting of Si, Ge, Sn and Pb), Mg 3 X2 2 (X2 is Sb and / or Bi), and X3Mg 2 X4 2(X3 is Ca and / or Yb, and X4 is Sb and / or Bi). These are known as semiconductor materials with thermoelectric properties, and the carrier type and concentration can be controlled by adding dopants.

[0024] The above Mg 2 X1 belongs to the cubic crystal system and the Fm-3m space group (space group 225 of the International Tables for Crystallography). Here, the "-" in "Fm-3m" indicates an overbar for m. For example, Mg 2 When X1 is grown on the c-plane (0001) of a sapphire substrate as an insulating substrate, a magnesium-based thermoelectric semiconductor with a (111) orientation is obtained, which has excellent thermoelectric properties. 3 X2 2 La 2 O 3 It has the X3Mg structure and belongs to the P-3m1 space group (164th in the International Tables for Crystallography). 2 X4 2 is CaAl 2 S 2 It has the above-mentioned structure and belongs to the P-3m1 space group (164th in the International Tables for Crystallography). Here, the "-" in "P3-m1" indicates an overbar of 3.

[0025] Undoped Mg 2 X1, undoped Mg 3 X2 2 and undoped X3Mg 2 X4 2 Both are narrow-gap semiconductors, and it is known that they can be n-type or p-type depending on the choice of elements, the amount of defects, etc.

[0026] The dopant added to the magnesium-based thermoelectric semiconductor 121 is appropriately selected depending on the thermoelectric semiconductor that is the parent phase. For example, Mg 2In Sn, it is known that by adding Sb, Bi, Al, etc., it becomes n-type. The addition amount is added within the range where the crystal structure is maintained.

[0027] The film thickness of the magnesium-based thermoelectric semiconductor 121 is not particularly limited, but preferably it may be 50 nm or more. There is no particular upper limit for the thickness, but for example, it may be 10 μm or less, and considering the microfabrication of the device, it may be 1 μm or less. From the perspective of manufacturing efficiency, it may be in the range of 50 nm or more and 1 μm or less. For example, a range of 200 nm or more and 400 nm or less may be adopted.

[0028] The magnesium-based thermoelectric semiconductor 121 may be amorphous, polycrystalline, or single crystal, but preferably it is an oriented film or a single crystal film. Thereby, excellent thermoelectric characteristics can be exhibited.

[0029] The silicon nitride film 130 is not limited as long as it is a film containing silicon (Si) and nitrogen (N), but it may be a film represented by SiN x (where x satisfies 0.6 < x < 1.4). The silicon nitride film 130 can function as an adhesion layer with excellent adhesion to the magnesium-based thermoelectric semiconductor 121, and in the lithography technology described later, the resist formed on the silicon nitride film 130 will not peel off.

[0030] The silicon nitride film 130 preferably has a thickness in the range of 5 nm or more and 250 nm or less. Within this range, it adheres firmly to the magnesium-based thermoelectric semiconductor 121. The silicon nitride film 130 more preferably has a thickness in the range of 180 nm or more and 220 nm or less. Within this range, it is particularly excellent as an adhesion layer.

[0031] An oxide layer may be present between the magnesium-based thermoelectric semiconductor 121 and the silicon nitride film 130. The oxide layer may include a natural oxide layer formed by exposing the magnesium-based thermoelectric semiconductor 121 to the atmosphere after production. In the present invention, even if a natural oxide layer is present, the above-mentioned silicon nitride film 130 improves adhesion, so that peeling of the resist during microfabrication can be avoided, and the yield can be improved.

[0032] More specifically, the oxide layer is an amorphous layer containing oxygen and the constituent elements of the magnesium-based thermoelectric semiconductor 121. The inventors of the present application have also discovered that the silicon nitride film 130 does not lose adhesion even if the magnesium-based thermoelectric semiconductor 121 has an oxide layer.

[0033] Such an oxide layer can be confirmed by identifying the elements by Auger electron spectroscopy and by the diffraction pattern by reflection high-energy electron diffraction images. The oxide layer has a thickness in the range of 0 nm to 50 nm. Note that since the oxide layer is extremely thin, it may be below the detection limit (50 nm) in normal film thickness measurements, but if its presence is confirmed by the above Auger electron spectroscopy and electron diffraction, it can be considered to have a thickness of 0 nm to 50 nm.

[0034] The second thermoelectric thin film 140 may be a metal material or a semiconductor material without any restrictions as long as it has thermoelectric properties different from those of the first thermoelectric thin film 120. For example, an n-type material selected from the group consisting of bismuth (Bi), nickel (Ni), cobalt (Co) and constantan (Cu-Ni), and a p-type material such as antimony (Sb) and / or nichrome (Ni-Cr) can be used as the second thermoelectric thin film 140. These are materials that can be formed at room temperature and have a relatively large thermoelectromotive force.

[0035] By selecting a material having a Seebeck coefficient of the second thermoelectric thin film 140 different from that of the magnesium-based thermoelectric semiconductor 121 of the first thermoelectric thin film 120, thermal energy can be converted into electricity, but it is preferable to select a material having a carrier type different from that of the magnesium-based thermoelectric semiconductor 121 of the first thermoelectric thin film 120. This allows for effective thermoelectric conversion. For example, when the magnesium-based thermoelectric semiconductor 121 exhibits p-type thermoelectric properties, the second thermoelectric thin film 140 can be made of a material exhibiting n-type thermoelectric properties, and when the magnesium-based thermoelectric semiconductor 121 exhibits n-type thermoelectric properties, the second thermoelectric thin film 140 can be made of a material exhibiting p-type thermoelectric properties.

[0036] The film thickness of the second thermoelectric thin film 140 is not particularly limited, but is preferably 50 nm or more. There is no particular upper limit to the thickness, but it may be, for example, 5 mm or less, and considering microfabrication of the element, it may be 1 mm or less, more preferably 10 μm or less, 1 μm or less. From the viewpoint of manufacturing efficiency, it may be in the range of 50 nm to 1 μm, for example, a range of 250 nm to 350 nm may be adopted.

[0037] The longitudinal length and width of the first thermoelectric thin film 120, which includes the magnesium-based thermoelectric semiconductor film 121 and the silicon nitride film 130, and the second thermoelectric thin film 130 are not particularly limited, but are illustratively in the ranges of 1 mm or more and 15 mm or less, and 5 μm or more and 40 μm or less, respectively.

[0038] The distance between the first thermoelectric thin film 120 and the second thermoelectric thin film 140 is not particularly limited, but may be in the range of 1 μm to 30 μm from the viewpoint of manufacturing efficiency.

[0039] The electrode 150 is not particularly limited as long as it electrically connects the magnesium-based thermoelectric semiconductor 121 and the second thermoelectric thin film 140, but is illustratively selected from the group consisting of a chromium (Cr) layer, a nickel (Ni) layer, and a platinum (Pt) layer. These materials are known as electrode materials.

[0040] The thickness of the electrode 150 is not particularly limited, but is preferably in the range of 50 nm to 1 μm. The film thickness is more preferably in the range of 50 nm to 500 nm. Within this range, a good quality film can be obtained and excellent electrical properties can be exhibited. For example, the film thickness can be in the range of 90 nm to 150 nm.

[0041] The electrode 150 preferably has a two-layer structure made of Cr and Ni thereon. Cr has excellent adhesion to the magnesium-based thermoelectric semiconductor film 121, and therefore has excellent electrical properties. Furthermore, the two-layer structure provides sufficient mechanical strength to allow wiring to a contact electrode (not shown) that generates a mechanical load without any problems. The electrode 150 more preferably has a three-layer structure made of Cr, Ni, and Pt. When the electrode has a two-layer or three-layer structure, the total thickness of the layers may be within the above range.

[0042] The thermoelectric conversion element 100 of the present invention may be covered with a silicon nitride film, except for the contact electrodes (see, for example, FIG. 10(A)) that connect to an external circuit (measuring instrument) (not shown). This protects the entire thermoelectric conversion element 100 and suppresses deterioration of the element's characteristics. Such a silicon nitride film may be the same as the silicon nitride film 130 described above.

[0043] Next, the operation of the thermoelectric conversion element 100 of the present invention will be briefly described. In Fig. 1, the magnesium-based thermoelectric semiconductor 121 of the first thermoelectric thin film 120 is a p-type thermoelectric material, and the second thermoelectric thin film 140 is an n-type thermoelectric material. The thermoelectric conversion element 100 of the present invention is placed in an environment where the electrode 150 at the top of the page is at a high temperature and the electrode at the bottom of the page is at a lower temperature. Next, when the electrodes at the ends of the thermoelectric conversion element 100 are connected to an external circuit (not shown) such as an external measuring instrument, a voltage is generated by the Seebeck effect, and a current flows as shown by the arrow in Fig. 1. In detail, the electrons in the n-type second thermoelectric thin film 140 obtain thermal energy from the high-temperature electrode 150, move to the low-temperature electrode, and release the thermal energy there, while the holes in the p-type first thermoelectric thin film 120 obtain thermal energy from the high-temperature electrode, move to the low-temperature electrode, and release the thermal energy there, causing a current to flow.

[0044] Next, a method for manufacturing the thermoelectric conversion element 100 of the present invention using lithography technology will be described. FIG. 2 is a flow chart showing the steps of manufacturing the flat thermoelectric conversion element of the present invention.

[0045] Step S210: A first thermoelectric thin film is formed on an insulating substrate by laminating a magnesium-based thermoelectric semiconductor film and then a silicon nitride film, and then patterned. Step S220: A second thermoelectric thin film is formed on an insulating substrate and patterned. Step S230: An electrode is formed to electrically connect the magnesium-based thermoelectric semiconductor film and the second thermoelectric thin film.

[0046] In this manner, by forming the silicon nitride film in step S210, adhesion to the resist is improved when using lithography technology, so that the resist is not peeled off even during the subsequent microfabrication processes such as exposing the magnesium-based thermoelectric semiconductor thin film and forming electrodes, and the thermoelectric conversion element of the present invention is manufactured.

[0047] Each step will be explained in detail below. FIG. 3 is a procedure showing the formation and patterning of the first thermoelectric thin film in step S210. It should be noted that Figs. 3 to 5 are schematic views for ease of understanding, and do not show the actual size of each element, and the relationships between each component element are not limited to those shown.

[0048] A magnesium-based thermoelectric semiconductor film 121 is formed on an insulating substrate 110 (structure A). Next, a silicon nitride film 130 is formed on the magnesium-based thermoelectric semiconductor film 121 by physical vapor deposition (structure B). Here, the insulating substrate 110, the magnesium-based thermoelectric semiconductor film 121, and the silicon nitride film 130 are as described above, and therefore a description thereof will be omitted. For the formation of the magnesium-based thermoelectric semiconductor film 121 and the silicon nitride film 130, a physical vapor deposition method (vacuum deposition method, molecular beam deposition method, PLD (Physical Laser Deposition) method by laser ablation, molecular beam epitaxy, various sputtering methods, etc.), a chemical vapor deposition method (MOCVD method, various CVD methods including flash CVD method, etc.), a chemical liquid phase deposition method (sol-gel method, metal organic compound decomposition (MOD) method, liquid phase mist film formation (LSMCD method, etc.) can be appropriately adopted.

[0049] A resist 310 is applied onto the obtained structure B (structure C). The resist 310 is a composition whose solubility in a developer changes when exposed to light or an electron beam, and is available in negative and positive types. Here, it is assumed that the resist 310 is a positive type photoresist whose solubility in a developer increases when exposed to light, and the irradiated portion is removed by development.

[0050] A rectangular pattern is drawn on the resist 310, for example, by a laser exposure device, and when developed, only the irradiated portions are removed (Structure D). Next, the portions where the resist is not applied are removed by reactive ion etching (RIE), ion milling, or the like. In this way, the first thermoelectric thin film is patterned (Structure E). In Structure E, the resist remains, but the resist may be removed by a remover, or the like.

[0051] FIG. 4 is a procedure showing the formation and patterning of the second thermoelectric thin film in step S220.

[0052] A resist 310 is applied to the structure E obtained in Fig. 3 (structure F). A rectangular pattern is drawn on the resist 310, for example, by a laser exposure device, so that only the area where the second thermoelectric thin film is to be formed is exposed, and when the resist is developed, only the irradiated area is removed (structure G).

[0053] Next, the second thermoelectric thin film 140 is formed by physical vapor deposition using an evaporator or the like on the substrate where only the region where the second thermoelectric thin film is to be formed is exposed (structure H). In consideration of the subsequent lithography technology and lift-off process, the second thermoelectric thin film is preferably formed at room temperature (a range of 8° C. to 35° C.). The above-mentioned material of the second thermoelectric thin film 140 is preferable because it is a material that can be formed at room temperature.

[0054] Next, when the resist 310 is removed with a remover or the like, the unnecessary second thermoelectric thin film is removed together with the resist, and the first thermoelectric thin film 120 and the second thermoelectric thin film 140 are positioned on the substrate 110 (structure I).

[0055] FIG. 5 is a procedure showing the formation of the electrodes in step S230.

[0056] A resist 310 is applied to the structure I obtained in FIG. 4 (structure J). In order to electrically connect the magnesium-based thermoelectric semiconductor film 121 and the second thermoelectric thin film 140, a part of the magnesium-based thermoelectric semiconductor film 121 of the first thermoelectric thin film 120 is exposed. For example, a rectangular pattern is drawn on the resist 310 by a laser exposure device, and when it is developed, only the irradiated part that is irradiated with light is removed (structure K). Next, the exposed silicon nitride film 130 of the first thermoelectric thin film is removed by reactive ion etching (RIE), ion milling, chemical etching, or the like (structure L).

[0057] Next, an electrode 150 is formed by physical vapor deposition such as electron beam evaporation on the substrate with a portion of the silicon nitride film 130 exposed (structure M). When the resist 310 is removed with a remover or the like, unnecessary electrodes are removed together with the resist, and at least a pair of the first thermoelectric thin film 120 and the second thermoelectric thin film 140 are positioned on the substrate 110, and the magnesium-based thermoelectric semiconductor film 121 of the first thermoelectric thin film 120 and the second thermoelectric thin film 140 are electrically connected by the electrode 150, thereby obtaining the thermoelectric conversion element 100 of the present invention.

[0058] 3 to 5, for simplicity, only a pair of the first thermoelectric thin film 120 and the second thermoelectric thin film 140 are shown, but the number of pairs is not limited to this. Also, with reference to FIGS. 2, 4, and 5, step S220 is shown to be performed after step S230, but step S220 may be performed after step S230. In this case, a part of the second thermoelectric thin film 140 is configured to be located above the electrode 150. Such a modification would be easily understood by a person skilled in the art.

[0059] Next, the present invention will be described in detail using specific examples, but it should be noted that the present invention is not limited to these examples. EXAMPLES

[0060] [Reference example 1] As a reference example 1, a magnesium-based thermoelectric semiconductor film was formed on a sapphire substrate ((0001) single crystal, 15 mm square, thickness = 0.43 mm, manufactured by Shinkosha Co., Ltd.) using a molecular beam epitaxy apparatus (EV-500 manufactured by Eiko Co., Ltd.). 2 A Sn thin film was formed to a thickness of 200 nm to 400 nm. The film formation conditions were the same as those described in Non-Patent Document 1. Next, this thin film was exposed to the air, and an oxide layer was formed on the surface.

[0061] The obtained thin film sample was subjected to Auger electron spectroscopy (Yamamoto Vacuum) and reflection high-energy electron diffraction (AVC RDA-001 type). The results are shown in Figure 6.

[0062] FIG. 6 shows an Auger electron spectroscopy spectrum and a reflection electron diffraction image of the thin film sample of Reference Example 1.

[0063] According to the Auger electron spectroscopy spectrum, carbon (C), oxygen (O) and magnesium (Mg) were detected at 0 minutes (immediately after the start of sputtering). Carbon was due to contamination on the surface of the thin film sample. As sputtering continued, O, Mg and Sn were detected at 9 and 30 minutes of sputtering, confirming the presence of an oxide layer. After 60 minutes of sputtering, O was not detected, and only Sn and Mg were detected, with Mg 2 The presence of a Sn film was confirmed. 2 It was found that a Sn film and an oxide layer containing Mg and Sn were laminated in this order.

[0064] The electron diffraction pattern of the oxide layer showed no spots or patterns and was found to be amorphous. 2 The electron diffraction image of the Sn film showed spots, indicating that it was an oriented film.

[0065] Although not shown, the thickness of the oxide layer was evaluated using a surface step gauge and found to be below the detection limit, indicating that the thickness of the oxide layer was greater than 0 nm and less than or equal to 50 nm.

[0066] In addition, Mg 2 The Auger electron spectroscopy spectrum and reflection electron diffraction image of a thin film sample that had been exposed to the atmosphere and then kept in a vacuum for six months were similarly measured, yielding the same results as in Figure 6. This shows that the thickness of the oxide layer will not increase further as long as it is kept in a vacuum.

[0067] [Example 1] In Example 1, the first thermoelectric thin film is Mg 2 A planar thermoelectric conversion element was fabricated using photolithography technology, which consisted of a laminated film of a Sn film, a silicon nitride film, and 131 pairs of Bi films as the second thermoelectric thin film.

[0068] FIG. 7 is a diagram showing the element structure of the flat thermoelectric conversion element of Example 1. As shown in FIG. FIG. 8 is a diagram showing details of the flat thermoelectric conversion element of Example 1. As shown in FIG.

[0069] In Example 1, as shown in Figs. 7 and 8, a MgO substrate with an oxide layer was used as an insulating substrate. 2 There were 131 pairs of the first thermoelectric thin film made of a laminated film of Sn film and silicon nitride film and the second thermoelectric thin film made of Bi film, each of which was electrically connected with an electrode of a two-layer structure of Cr and Ni. The size of the thermoelectric conversion element and each component was as shown in Figures 7 and 8.

[0070] FIG. 9 shows a procedure for manufacturing the planar thermoelectric conversion element of Example 1. It should be noted that FIG. 9 is a schematic diagram for ease of understanding, and does not show the actual size of each element, and the relationship between each component is not limited to this.

[0071] FIG. 9 shows a manufacturing process of a pair of first and second thermoelectric thin films in a CD cross-sectional view. Step S210 (Fig. 2): A magnesium-based thermoelectric semiconductor film, Mg, was deposited on a sapphire substrate 910 ((0001) single crystal, 15 mm square, thickness = 0.43 mm, manufactured by Shinkosha Co., Ltd.). 2 A Sn film 920 and then a silicon nitride film 930 were formed and patterned.

[0072] In detail, a molecular beam epitaxy apparatus (EV-500, manufactured by Eiko Co., Ltd.) was used to deposit Mg 2 The Sn film 920 was formed to a thickness of 200 nm to 400 nm. The film formation conditions were the same as those described in Non-Patent Document 1.

[0073] Next, this thin film was once exposed to the atmosphere, and then a silicon nitride film 930 was formed to a thickness of 200 nm by reactive DC sputtering using a sputtering device (Shibaura Mechatronics Corporation, CFS-4EP-LL). The sputtering conditions were as follows. 2When the Sn film is exposed to the atmosphere, an oxide layer is formed on the surface. See Reference Example 1 for the thickness of this oxide layer. Target: Si target (φ=300mm) Target-substrate distance: 100mm Back pressure: 10 -4 Pa or less Sputtering gas pressure: 0.5Pa Sputter gas: argon and nitrogen DC power: 200W Substrate heating: room temperature

[0074] The obtained silicon nitride film 930 is an amorphous film containing Si and N (SiN x ) was.

[0075] The resulting SiN x / Mg 2 A resist 940 (OFPR800LB, manufactured by Tokyo Ohka Kogyo Co., Ltd.) was applied to the Sn / sapphire laminated structure, and the resist was patterned using a maskless exposure device (DL-1000, manufactured by Nano System Solutions Co., Ltd.) ([1-1] in Figure 9).

[0076] Next, in the area where the resist was not applied, SiN was removed by reactive ion etching (ULVAC, Inc., CE-300I). x The film was etched and the Mg 2 The Sn film was etched ([1-2] in Fig. 9). The resist was removed by immersing it in a resist remover (RemoverPG, manufactured by MicroChem) ([1-3] in Fig. 9).

[0077] Step S230 (Fig. 2): Mg 2 An electrode 150 was formed to electrically connect the Sn film 920 and the Bi film 930. Here, in FIG. 2, step S230 was carried out prior to step S220.

[0078] In detail, a resist (OFPR800LB, manufactured by Tokyo Ohka Kogyo Co., Ltd.) was applied again to the structure shown in [1-3] of FIG. 9, and the resist was patterned using a maskless exposure device ([2-1] of FIG. 9).

[0079] The SiN x The film 930 was etched by reactive ion etching ([2-2] in FIG. 9). The film was immersed in a resist removal solution to remove the resist ([2-3] in FIG. 9).

[0080] A resist (OFPR800LB, manufactured by Tokyo Ohka Kogyo Co., Ltd.) was applied again to the structure shown in [2-3] of Figure 9, and the resist was patterned using a maskless exposure device ([3-1] of Figure 9). This exposed the areas where electrodes were to be provided.

[0081] An electron beam deposition apparatus (UEP-3000BS, manufactured by ULVAC, Inc.) was used to form an electrode 950. At this time, the electrode 950 had a two-layer structure of Cr (10 nm) and Ni (100 nm) ([3-2] in FIG. 9).

[0082] The substrate was immersed in a resist remover to remove the unnecessary electrodes together with the resist ([3-3] in Figure 9). This method is also called lift-off. 2 An electrode 950 for electrically connecting the Sn film 920 and the Bi film 930 was formed.

[0083] Step S220 (FIG. 2): A Bi film 960 is formed on a sapphire substrate 910 and patterned.

[0084] A resist (CLARIANT, AZ5214E) was applied to the structure shown in [3-3] of Figure 9, and the resist was patterned using a maskless exposure device ([4-1] of Figure 9). This exposed the area where the Bi film was to be applied.

[0085] Next, a Bi film 960 was deposited to a thickness of 300 nm at room temperature (20° C.) using an evaporator (ULVAC, VTS-350M). At this time, a part of the Bi film 960 was deposited on the previously formed electrode 950, so that the Bi film 960 was exposed to the Mg 2 It is electrically connected to the Sn layer 920 .

[0086] This was immersed in a resist remover to remove the unnecessary Bi film 960 together with the resist ([4-3] in FIG. 9). In this manner, the thermoelectric conversion element of Example 1 was formed. The entire thermoelectric conversion element (excluding the contact electrodes) was then covered with a further SiN x The thermoelectric conversion element of Example 1 was observed under a microscope. The results are shown in FIG.

[0087] FIG. 10 is a diagram showing the results of microscope observation of the flat thermoelectric conversion element of Example 1.

[0088] FIG. 10(B) shows an enlarged view of FIG. 10(A). According to FIG. 10, no peeling of the electrodes was observed, and it was found that a high-quality planar thermoelectric conversion element was obtained using photolithography technology. Although not shown, when the electrodes were made of only Ni (100 nm), some peeling of the electrodes was observed during the process. This shows that the use of Cr improves adhesion. In addition, when the electrodes were made to have a three-layer structure of Ni (100 nm), Cr (100 nm), and Pt (10 nm) instead of the two-layer structure of Cr (10 nm) and Ni (100 nm), an even higher quality planar thermoelectric conversion element was obtained.

[0089] [Example 2] In Example 2, the first thermoelectric thin film is Mg 2 A planar thermoelectric conversion element using 131 pairs of Sn film and Bi film as the second thermoelectric thin film was manufactured by photolithography technology. The same as in Example 1 except that the silicon nitride film was not formed.

[0090] However, Mg 2A resist was applied onto the Sn film, patterned, and then ion milling was performed, but the resist peeled off during milling, making it impossible to carry out any further processes.

[0091] The results of Examples 1 and 2 show that by providing a silicon nitride film on a magnesium-based thermoelectric semiconductor film, even if there is a natural oxide layer, the adhesion between the resist and the magnesium-based thermoelectric semiconductor film is improved, so that the resist does not peel off even during the subsequent microfabrication processes such as exposure of the magnesium-based thermoelectric semiconductor thin film and electrode formation, and high-quality flat thermoelectric conversion elements can be provided with good yield. Those skilled in the art will naturally understand that even in the absence of a natural oxide layer, the adhesion between the resist and the magnesium-based thermoelectric semiconductor film is improved by the silicon nitride film.

[0092] [Example 3] In Example 3, the first thermoelectric thin film was a Mg 2 A flat thermoelectric conversion element using seven pairs of Sn film and Bi film as the second thermoelectric thin film was manufactured using photolithography technology. Except for the number of pairs, it was the same as Example 1. The thermoelectric conversion element of Example 3 was of high quality, with no peeling of the resist or the electrodes during milling, just like Example 1.

[0093] A temperature difference was applied between the electrodes of the flat thermoelectric conversion element of Example 3, and the element characteristics (power generation) were evaluated. A temperature difference of 10K to 110K (constant 300K on the low-temperature side, 310 to 410K on the high-temperature side) was applied 11 times to both ends of the element, and the heat cycle was repeated. The internal resistance was measured before and after the heat cycle, and the amount of change was examined. As a result, the internal resistance value of the thermoelectric conversion element of Example 3 after the heat cycle was 1.01, normalized to 1 before the heat cycle. In other words, no significant deterioration of the element characteristics was observed even after the heat cycle.

[0094] This suggests that in the flat thermoelectric conversion element of the present invention, a good interface is maintained between the magnesium-based thermoelectric semiconductor film and the silicon nitride film in the first thermoelectric thin film, and it was shown that the element characteristics do not deteriorate. [Industrial Applicability]

[0095] The flat thermoelectric conversion element of the present invention can be applied to an independent power source or a sensor element for IoT devices. The manufacturing method of the flat thermoelectric element of the present invention has excellent adhesion, which is advantageous for microfabrication and high yield. [Explanation of symbols]

[0096] 100 Planar thermoelectric conversion element 110 Insulating substrate 120 First Thermoelectric Thin Film 121 Magnesium-based thermoelectric semiconductor film 130, 930 Silicon nitride film 140 Second Thermoelectric Thin Film 150, 950 electrodes 310, 940 Resist 910 Sapphire Substrate 920 mg 2 Sn film 960 Bi membrane

Claims

1. An insulating substrate; At least a pair of a first thermoelectric thin film and a second thermoelectric thin film located on the insulating substrate; an electrode connecting the first thermoelectric thin film and the second thermoelectric thin film; Equipped with the first thermoelectric thin film comprises a magnesium-based thermoelectric semiconductor film and a silicon nitride film located on the magnesium-based thermoelectric semiconductor film; an oxide layer is present between the magnesium-based thermoelectric semiconductor film and the silicon nitride film; The magnesium-based thermoelectric semiconductor film is made of a material selected from the group consisting of doped or undoped Mg 2 X1 (X1 is at least one element selected from the group consisting of Si, Ge, Sn, and Pb), Mg 3 X2 2 (X2 is Sb and / or Bi), and X3Mg 2 X4 2 (X3 is Ca and / or Yb, and X4 is Sb and / or Bi); The electrodes electrically connect the magnesium-based thermoelectric semiconductor film of the first thermoelectric thin film and the second thermoelectric thin film of the planar thermoelectric conversion element.

2. 2. The flat thermoelectric conversion element according to claim 1, wherein the silicon nitride film has a thickness in the range of 5 nm to 250 nm.

3. 2. The flat thermoelectric conversion element according to claim 1, wherein the oxide layer is amorphous and contains oxygen and elements that constitute the magnesium-based thermoelectric semiconductor film.

4. The flat thermoelectric conversion element according to claim 1 , wherein the oxide layer has a thickness in the range of more than 0 nm and not more than 50 nm.

5. 5. The flat thermoelectric conversion element according to claim 1, wherein the magnesium-based thermoelectric semiconductor film is oriented.

6. 6. The flat thermoelectric conversion element according to claim 1, wherein the magnesium-based thermoelectric semiconductor film has a thickness in the range of 50 nm to 10 μm.

7. 7. The flat thermoelectric conversion element according to claim 1, wherein the electrodes have a laminated structure in which a chromium layer and a nickel layer are laminated in this order when viewed from the insulating substrate side.

8. 8. The flat thermoelectric conversion element according to claim 1, wherein the second thermoelectric thin film is made of a metal material or a semiconductor material.

9. The flat thermoelectric conversion element according to any one of claims 1 to 8, wherein the flat thermoelectric conversion element is further covered with a silicon nitride film, except for an electrode connected to an external circuit.

10. A method for manufacturing the flat thermoelectric conversion element according to any one of claims 1 to 9 by using a lithography technique, comprising the steps of: forming a first thermoelectric thin film in which a magnesium-based thermoelectric semiconductor film and then a silicon nitride film are laminated on an insulating substrate, and patterning the first thermoelectric thin film; forming and patterning a second thermoelectric thin film on the insulating substrate; forming an electrode that electrically connects the magnesium-based thermoelectric semiconductor film and the second thermoelectric thin film; Inclusive of The magnesium-based thermoelectric semiconductor film is made of a material selected from the group consisting of doped or undoped Mg 2 X1 (X1 is at least one element selected from the group consisting of Si, Ge, Sn and Pb), Mg 3 X2 2 (X2 is Sb and / or Bi), and X3Mg 2 X4 2 (X3 is Ca and / or Yb, and X4 is Sb and / or Bi).

11. 11. The method of claim 10, wherein forming and patterning the first thermoelectric thin film further comprises exposing the magnesium-based thermoelectric semiconductor film to air prior to forming the silicon nitride film.

12. 12. The method of claim 10 or 11, wherein forming and patterning the second thermoelectric thin film forms the second thermoelectric thin film at room temperature.

13. The method according to any one of claims 10 to 12, further comprising covering the electrodes, except for the electrodes connected to an external circuit, with a further silicon nitride film following the formation of the electrodes.

Citation Information

Patent Citations

  • Thermoelectric conversion device

    JP2016187008A

  • Sheet-like thermoelectric conversion device and manufacturing method therefor

    JP2017069375A

  • Flexible Thermoelectric Module

    JP2019525455A

  • Photovoltaic power generation module

    WO2014171146A1

  • Thermoelectric conversion element and thermoelectric conversion module

    WO2016039022A1